Prenatal Oxycodone Exposure Alters CNS Endothelin Receptor Expression in Neonatal Rats - Devarapalli, M.; Leonard, M.; Briyal, S.; Stefanov, G.; Puppala, B. L.; Schweig, L.; Gulati, A. (Drug Research, 2016)
Prenatal opioid exposure such as oxycodone is linked to significant adverse effects on the developing brain. Endothelin (ET) and its receptors are involved in normal development of the central nervous system. Opioid tolerance and withdrawal are mediated through ET receptors. It is possible that adverse effect of oxycodone on the developing brain is mediated through ET receptors. We evaluated brain ETA and ETB receptor expression during postnatal development in rats with prenatal oxycodone exposure. Timed pregnant Sprague-Dawley rats received either oxycodone or placebo throughout gestation. After birth, male rat pups were sacrificed on postnatal day (PND) 1, 7, 14 or 28. Brain ETA and ETB receptor expression was determined by Western blot analysis. Oxycodone pups compared to placebo demonstrated congenital malformations of the face, mouth, and vertebrae at the time of birth [4/69 (5.7%) vs. 0/60 (0%); respectively] and intrauterine growth retardation [10/69 (15%) vs. 2/60 (3.3%); respectively]. On PND 28, oxycodone pups compared to placebo had lower body and kidney weight. ETA receptor expression in the oxycodone group was significantly higher compared to placebo on PND 1 (p=0.035), but was similar on PND 7, 14, or 28. ETB receptor expression decreased in oxycodone compared to placebo on PND 1 and 7 (p=0.001); and increased on PND 28 (p=0.002), but was similar on PND 14. Oxycodone-exposed rat pups had lower birth weight and postnatal weight gain and greater congenital malformations. ETB receptor expression is altered in the brain of oxycodone-treated rat pups indicating a possible delay in CNS development.
Keywords: opioid; endothelin; CNS; postnatal development; ETA receptors; ETB receptors